Skin malformations in a neonatal foal tested homozygous positive for Warmblood Fragile Foal Syndrome - Monthoux, Chloé; de Brot, Simone; Jackson, Michelle; Bleul, Ulrich; Walter, Jasmin (BioMed Central, 2015)
BACKGROUND: